(untitled) (Journal of Health Sciences, 2018)
Introduction: The most common health problem associated with the negative effect of heavy school bags is back pain, and non-specific back pain is frequently observed in childhood. The prevalence of back pain in schoolchildren varies from 12% to 92%, depending on the age and affected region of the back. To prevent the occurrence of back pain in schoolchildren, the weight of school bag should not exceed 10% of the child’s body mass.Methods: This was a descriptive, cross-sectional study conducted in April 2017. We included 79 students of the fifth and sixth grade from the elementary school in Sarajevo. Information on the weight and type of school bag, method of carrying a school bag, and feelings of pain and tiredness due to school bag were obtained by questionnaire.Results: In the total sample, the majority of the students (64.6%) reported occasional back pain while carrying the bag, 20.3% of students reported no back pain, and 11.4% of students experienced frequent back pain. The mean school bag weight in the fifth grade was 4.01 ± 0.57 kg, and it was significantly higher (4.61 ± 0.86 kg) in the sixth grade. About 48.5% of the students in the fifth and 50% in the sixth grade carried school bags weighing more than 10% of the body mass. A higher mean weight of school bag was significantly more frequent in students who reported always feeling tired (11.03 ± 2.74%) compared to those who did not feel tired while carrying the school bag (8.41 ± 2%).Conclusions: Overall, more frequent occurrence of back pain and tiredness in schoolchildren was associated with heavier school bags (>10% of the body mass), and the occurrence of back pain due to school bag was related to gender (i.e., back pain was more common in girls compared to boys).